Antipsiquiatría: Deconsctrucción del concepto de enfermedad mental y crítica de la "razón psiquiátrica" - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The origin of psychiatric detention, the history of madness and excessive medicalization of our society farmacráticas and the complex relationship between psychiatry, law and pharmaceutical corporations, in a game of interest and collusion have led to the "humanization of the sentence. " That is, the use of "insanity" as criminal atenueante difficult to discern a boundary between the legal and ethical. Just here arises from the label "mental illness", the possible undoing of the criminal liability of a person who is allegedly incapacitated to act for himself in the legal field. Thus the mental health facility before us today as an instance of embracing powers, with telesurveillance devices, pointing to the previously announced formation of a 'thought police', whose presence and commanding voice are heard to peremptorily in institutions such as education, work and other areas where what is at stake is the scope of civil liberties, so the clinic has been delimited in civil difficult to discern a boundary between normality and abnormality.
Keywords: Psychiatry; madness; mental illness; schizophrenia; anti-psychiatry; social repression; illness